The Effect of Religious Maturity on Substantive Religiosity of Prospective PAI Teacher Students - Selvia, Sasmi; Rahmat, Munawar; Anwar, Saepul (ISLAMIKA, 2025)
Religious maturity and substantive religiosity are critical components in shaping the character and pedagogical orientation of prospective Islamic Religious Education (PAI) teachers. Teachers who exhibit mature religiosity and internalized religious values are more likely to foster religious character development among their students through reflective thought, ethical conduct, and value-oriented teaching practices. This study examines the level of religious maturity and its influence on the substantive religiosity of PAI teacher candidates in West Java, Indonesia. Employing a quantitative correlational design, data were collected through a structured questionnaire administered to 192 PAI teacher candidates from three universities using a convenience sampling method. The collected data were analyzed using SPSS software to perform correlation analysis. Descriptive results indicated that 60% of participants demonstrated a moderate level of religious maturity, while 96% exhibited high levels of substantive religiosity. Correlation analysis revealed a statistically significant and strong positive relationship between religious maturity and substantive religiosity, with a correlation coefficient of r = 0.631 and a significance level of p < 0.001, confirming the hypothesis at the 99% confidence level. These findings underscore the importance of fostering both cognitive and affective dimensions of religiosity in teacher education. The study recommends the development of a more integrative PAI curriculum that emphasizes value-based learning, spiritual reflection, and personal religious development to support the formation of ethically grounded and pedagogically competent future educators.